The Effect of Person-Job Fit And Work-Life Balance As Well As Job Involvement on The Performance of Employees of The Ombudsman of The Republic of Indonesia At The Representative office - Denny Christyanto, Frederikus; Tricahyadinata, Irsan; Lestari A.S, Dirga (International Journal of Science, Technology & Management, 2025)
This study aims to analyse the influence of Person Job Fit and Work Life Balance as well as Job Involvement on Employee Performance at Representative Offices. At the Indonesian Ombudsman, Assistant Ombudsmen are employees who support the Ombudsman in carrying out their supervisory functions in the provision of public services. The influence between variables was measured using the Structural Equation Modelling - Partial Least Square 4 approach. Data was collected by distributing questionnaires to 48 Ombudsman employees (Assistants) at the Representative Office. The results of the study indicate that Person Job Fit has a significant influence on Job Involvement and Employee Performance. Work-Life Balance also shows a significant influence on Employee Performance but does not show a significant influence on Job Involvement. While Job Involvement can act as a mediator between Person-Job Fit and Employee Performance, it cannot act as a mediator between Work-Life Balance and Employee Performance. Thus, job fit, which includes skills, interests, values, experience, and expectations, can help an Ombudsman employee achieve their individual performance. The achievement of performance from this job fit can also be supported through Job Involvement from the aspects of emotional involvement, cognitive involvement, work motivation, and job satisfaction.